The Influence of Age and Gender on the Esthetic Preference for the Shape of Maxillary Anterior Teeth - Hanif Ullah, Farhan Raees, Maryam Dil, Rozeena Farooq, Hanzala Waqar, Muhammad Haseebullah Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: An esthetic smile comes from various smile elements and requires knowing the complexities that control the equilibrium between teeth and soft tissues. In all dentistry areas, especially in prosthodontics and restorative dentistry, restoring a natural dental appearance has gained a lot of importance. This study’s results will lead us to the popular esthetic choices for forming anterior maxillary teeth among Khyber Pakhtunkhwa patients Aim: To determine the esthetic preference for the shape of maxillary anterior teeth. Study design: Descriptive cross-sectional study. Place and duration of study: Department of Prosthodontics, Sardar Begum Dental College & Hospital, Peshawar from 17th July 2021 to 17th January 2022. Methodology: After taking the study’s approval from the hospital ethical review committee board, 196 patients reporting to the Prosthodontics Department who fulfilled the inclusion criteria were invited to participate in the study. Patients were shown photograph displaying only maxillary teeth having three primary forms of five distinct incisor varieties, i.e., square (S), oval (O), triangular (T), and the two different maxillary teeth form: tapered-ovoid (TO) and square- tapering (ST). Results: The frequency of esthetic preference, 55(28.1%) patients had square incisor ‘S’, 23(11.7%) patients had ovoid incisors ‘O’, 44(22.4%) had triangular incisors ‘T’, 34(17.3%) patients had square tapered ‘ST’ while 40(20.4%) patients had tapered ovoid ‘TO’ esthetic preference. Practical Implication: Dentists preferred square-round incisors. In the study, there are some lay people does not discriminate between incisors shape for women. Dentists preferred square-round incisors. In the study, there are some lay people does not discriminate between incisors shape for women. Conclusion: Female patients of younger age group were affected by their esthetic perception of the shapes of the maxillary anterior teeth as compared to the male patients of the same group and most of the patients had square incisor ‘S’ as their choice of esthetic preference. Key words: Esthetic smile, Esthetic preference, Maxillary anterior teeth